Human Rights: Facts or Myths in Indonesia Era of Society 5.0 - Napitupulu, Widya Margareth (Universitas Negeri Semarang, 2023)
In this era of Society 5.0, humans are required to create new values so that they can avoid inequality. Both from an economic and social point of view. However, if examined more closely, there is one point that can’t be missed in human attention. That is human rights. Human Rights (HR) is something that is very attached to every human person. Human rights include the right to life and to get justice. Among these rights, there is also the right to be independent which guarantees every human being to be free to do or have an opinion both behind and in front of the to the development of the times. On the basis of the principle of “lex posterior derogat legi priori”, the old laws no longer apply. However, even though many new laws have been implemented, human rights problems have not stopped and have received significant solutions. Even today, there are still many human rights violations in this country. Using a qualitative method, this article will explain about human rights violations that are very worrying in Indonesia.